ENGARUH KEPEMILIKAN MANAJERIAL, INSTITUSIONAL, DIVIDEN, PERTUMBUHAN PERUSAHAAN, FREE CASH FLOW DAN PROFITABILITAS TERHADAP KEBIJAKAN HUTANG PERUSAHAAN - Hastutie Noor Andriati; Rouli Simbolon (Jurnal Akuntansi dan Keuangan Daerah, 2016)
The purpose of this study was to investigate the managerial ownership, institutional ownership, dividends, growth, free cash flow and profitability of the company's debt policy. This study uses a quantitative approach to the study population are companies that belong to the nonfinancial sector listed in Indonesia Stock Exchange in 2012, 2013, 2014 and 2015. Of the company's 523 population, 31sampel obtained by purposive sampling method. The results showed that partially managerial ownership, profitability, and free cash flow influence on the policy of corporate debt. Meanwhile, institutional ownership, dividend and firm growth policy does not have infuence the company's debts. In this study the researchers conducted additional tests that different test against corporate debt policy is proxied by DER (Debt to Equity Ratio), which is to see whether there is a difference between the debt policy in the company's service sector companies manufacturing sector. Different test results indicate that there is no difference between the debt policy of manufacturing companies and service companies.Kata kunci: Debt Ratio, insider ownership, institutional ownership, dividend, firm growth, profitability, free cash flow.